DETEKSI PERTUMBUHAN DAN PERKEMBANGAN BALITA MELALUI PENGGUNAAN BUKU KIA - Dardjito, Endo; Sistiarani, Colti; Nurhayati, Siti (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2014)
ABSTRACT MCH handbook has the function between the recording function, the function of education and communication functions. MCH handbook is a tool to monitor the growth and development of infants. Event detection is done in PosyanduPuspitasari dan Posyandu WatugedeKalibagor village. This type of research is a descriptive study through a cross sectional study approach. The sampling technique is through consequtive Sampling. The total sample obtained in this period as much as 48 toddlers. The instrument used, among others, check the detection of growth and development. Check the detection of growth by using a Health Card (KMS) contained in the KIA book. Check the progress detection using a reference stage of development in the KIA book. Infant growth status assessment results in PosyanduWatugede 72%, as much as 58.3% PosyanduPuspitasari accordance with minimum weight gain according to the existing KMS KIA book. Results of the assessment in the status of early childhood development as much as 91.7% posyanduwatugede, posyanduPuspitasari 100% included in the category of normal development. The importance of the use of the book in an effort KIA detection of growth and development. Keyword : growth, development, toddler, book  Kesmasindo, Volume 6, ( 3) Januari 2014, Hal. 166-175